(3GdLhGgQ hGdGMLGQs - (3CMeO Hf jhSa GdJjaGTj, TgGH GdOjf CHh GdYHGS,J (B651 (3g` s ((3eMeO Hf CMeO GdaQfhj GdecJH s)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb aShj hbOQ agOj aEfj LeYJ aj cJGHj gPG GcJH GdGMLGQ ef YOI cJH hGdLejY jUahf ef bhd fhQ GdYde s
(3BNQgG (B:s
(3EfgG UhQI GdchcH aj Gdadc adJYde Gfg de fQO HgG dYH hdG YHK hgPG eG GfJgj EdjfG s
(3HQSe GdSdWGf Gdedcj GdGTQaj GHj GdfUQ bGjJHGjs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3GjGUhajG (B(3611) s
Keywords: (3GdcjejGA h GdWHjYjGJs